Idiopathic Neonatal Haemochromatosis: A Case Report - Besharat, S; Alaee, E; Zahedpasha, Y (Journal of Nepal Paediatric Society, 2011)
A case of neonatal hemochromatosis is reported in a premature 35-week infant who presented at birth with coffee ground vomiting and gradual appearance of grayish icter and colorless stool. Neonatal hemochromatosis was confirmed by elevated ferritin levels and extrahepatic siderosis detected in liver biopsy. Key words: Neonatal hemochromatosis; Liver biopsy; Serum ferritin DOI: http://dx.doi.org/10.3126/jnps.v31i3.4966 J Nep Paedtr Soc 2011;31(3): 247-248